Pengaruh Standar Operasional Prosedur Rekrutmen Pegawai terhadap Kinerja Pegawai melalui Kebijakan Pimpinan sebagai Variabel Mediasi di Koperasi Karya Bakti Nusantara - Eseromo Daeli; Yelis Pristiono Gulo (Universitas Muhammadiyah Surabaya, 2024)
This study discusses the impact of Standard Operating Procedures for Employee Recruitment on employee performance through leadership policies as a mediating variable in Karya Bhakti Nusantara Cooperative. The formulation of the problem is how much influence Standard Operating Procedures of Employee Recruitment on employee performance through leadership policy as a mediating variable in Karya Bhakti Nusantara Cooperative. The purpose of this study was to determine the extent to which Standard Operating Procedures for Employee Recruitment affect employee performance through leadership policies as a mediating variable in Karya Bhakti Nusantara Cooperative. In this study, the population and sample consisted of all 19 employees at Karya Bhakti Nusantara Cooperative. The research method used is quantitative method with data collection using Likert scale questionnaire. The data were processed using SPSS version 26.0 through validity test, reliability test, normality test, multicollinearity test, and hypothesis testing. The results showed that employee recruitment SOP has a significant influence on employee performance, with an influence of 70.2%. In this context, it can be concluded that the implementation of good standard operating procedures (SOPs) in the employee recruitment process can contribute to improving employee performance through improving work quality, quantity, timeliness, cost efficiency, and the need for supervision. However, it should be noted that there are other factors that are not taken into account in this study (such as the epsilon factor) that have a significant impact of 29.8% on employee performance. Therefore, the results show that the proposed hypothesis can be accepted in the Karya Bhakti Nusantara Cooperative environment.